LncRNAs: Proverbial Genomic “Junk” or Key Epigenetic Regulators During Cardiac Fibrosis in Diabetes? - Biswas, Saumik; Thomas, Anu Alice; Chakrabarti, Subrata (Frontiers in Cardiovascular Medicine, 2018)
Long non-coding RNAs (lncRNAs) are critical regulators in a multitude of biological processes. Recent evidences demonstrate potential pathogenetic implications of lncRNAs in diabetic cardiomyopathy (DCM); however, the majority of lncRNAs have not been comprehensively characterized. While the precise molecular mechanisms underlying the functions of lncRNAs remain to be deciphered in DCM, emerging data in other pathophysiological conditions suggests that lncRNAs can have versatile features such as genomic imprinting, acting as guides for certain histone-modifying complexes, serving as scaffolds for specific molecules, or acting as molecular sponges. In an effort to better understand these features of lncRNAs in the context of DCM, our review will first summarize some of the key molecular alterations that occur during fibrosis in the diabetic heart (extracellular proteins and endothelial-to-mesenchymal transitioning), followed by a review of the current knowledge on the crosstalk between lncRNAs and major epigenetic mechanisms (histone methylation, histone acetylation, DNA methylation, and microRNAs) within this fibrotic process.